Pengembangan e-modul interaktif berbasis strategi heuristik vee untuk melatih kemampuan literasi numerasi siswa - Aidah Murdikah; Hepsi Nindiasari; Novaliyosi Novaliyosi (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2022)
Abstract: An interactive e-modul interaktife is a module in the form of a combination of two or more media (audio, text, graphics, images, animation and video) that are interactive, to convey a material, method, boundaries, and learning evaluation that is systematically designed and interesting, which can then cause a two-way relationship between the e-modul interaktife and its users. The interactive e-modul interaktife given to students must be a good and quality e-modul interaktife. Quality e-modul interaktifes can build, trigger, strengthen students' interest in learning independently and the learning process is more effective, efficient so that there is an improvement in the quality of learning. For this reason, the purpose of this research is to produce an interactive e-modul interaktife based on a valid, practical and effective heuristic strategy to train students' numeracy literacy skills, with the material used is geometry transformation. This type of research research is a development research (R&D) with a 4-D design of defining (Define), design (Design), development (Development), and dissemination (Dissemination). The subjects of this study were class XI mipa students of Al-Qudwah Integrated High School which totaled 21 students. The type of data taken is in the form of quantitative data and qualitative data, qualitative data in this study were collected using expert validity questionnaires, student response questionnaires, and quantitative data in this study were taken from numeracy literacy test instruments. Based on the results of the analysis obtained an average total validation (RTV) score from media experts 4.49 with very valid categories, material experts 4.56 with very valid categories, educational experts 4.65 with very valid categories, user response percentage 83%, this indicates that student responses to learning using interactive e-modul interaktifes based on heuristic strategies are of positive value, so that interactive e-modul interaktifes can be declared practical. Students' numeracy literacy skills after using this interactive e-modul interaktife based on heuristic strategies got a total average of 2.98 with excellent categories. Based on the results of the data analysis, it can be concluded that the interactive e-modul interaktife based on the vee heuristic strategy developed is suitable for use as an effective learning resource to train students' numeracy literacy skills on the topic of geometric transformation. This e-modul interaktife makes it easy for students to access flexible learning resources anywhere and anytime